Biomolecular condensation of intrinsically disordered regions in P. falciparum and H. sapiens transcription factors - Karamanof, Leonidas Marthinus (Department of Molecular and Cell Biology, 2023)
Plasmodium falciparum is still a major cause of disease and death, especially in sub-Saharan Africa. The organism's complex life cycle is tightly coupled to a carefully controlled gene expression programme, and its highly divergent transcriptional machinery suggests unique mechanisms of transcriptional control. Biomolecular condensation, driven by intrinsically disordered regions (IDRs) in proteins, has emerged as a previously underappreciated mechanism of cellular compartmentalisation and regulation. The study of eukaryotic transcription has been revolutionised by the understanding that biomolecular condensates formed by transcription factors play a key role in transcriptional regulation. The study these of so-called transcriptional condensates has so far not addressed the role of the general transcription factors (GTFs) and has not investigated the phenomenon in non-model eukaryotes such as P. falciparum. Here we report on the biochemical purification and functional characterisation of an ensemble of TF-IDR fluorescent protein fusion constructs, using fluorescence microscopy. During the course of this work, we established a standardised data acquisition, analysis and visualisation pipeline for fluorescence microscopy images. Bioinformatic analysis uncovered unique sequence characteristics of the P. falciparum RPB1 C-terminal domain (PfRPB1-CTD) that suggest a functionally divergent role in biomolecular condensation. This work demonstrates that the PfRPB1-CTD, as well as a panel of GTF-IDR fusion proteins, including P. falciparum (Pf) and Homo sapiens (Hs) TATA-binding protein-IDR (TBP), TFIIAαß-IDR and TFIIFß-IDR can drive biomolecular condensation in vitro. Comparative analyses show that PfRPB1-CTD and PfTBP-IDR drive biomolecular condensation at much lower protein concentrations than homologous regions from H. sapiens, suggesting a potential role in organising P. falciparum transcriptional condensates. This work further expands on the characterisation of the IDR from the largest subunit of the Mediator complex, MED1-IDR. Our results underscore its status as a strong driver of biomolecular condensation and further show that the material properties of MED1-IDR condensates are affected by a range of environmental conditions. Finally, we report on the compatibility of P. falciparum and H. sapiens proteins to form mixed condensates. We demonstrate that both PfRPB1-CTD and MED1-IDR exhibit wide-ranging compatibility with GTF-IDR fusion proteins, that are recruited to and concentrated in mixed assemblies. However, while MED1-IDR recruits HsRPB1-CTD to form homogenously mixed transcriptional condensates, PfRPB1-CTD and MED1- IDR form heterogenous mixed condensates, in which the two protein components form separate compartments. This result provides first evidence that transcriptional condensates formed in human cells and in the malaria parasite may have distinct properties and thus may provide a highly promising target for the much needed development of new antimalarial drugs.